Towards Marine Ecosystem-Based Management in the Wider Caribbean - Fanning, Lucia; Mahon, Robin; McConney, Patrick; Verhart, L. (MARE Publication Series, 2011)
In order to ensure sustainable use of their shared marine resources, the nations of the West Caribbean Region must adopt an approach that encompasses both the human and natural dimensions of ecosystems. This volume directly contributes to that vision, bringing together the collective knowledge and experience of scholars and practitioners within the wider Caribbean to assemble a road map towards marine ecosystem based management for the region. The research presented here will be used not only as a training tool for graduate students, but also as comparative example and guide for stakeholders and policy makers in each of the world's sixty-four large marine ecosystems.